Change and continuity in the international globalization process : turn of the century scenarios - SELA (SELA CaracasVE, 1996)
Examines the main elements of change in contemporary political order. Evaluates the main aspects of globalization in the areas of market process as well as political phenomena and space. Describes four alternate scenarios, long- and mid-term giving special emphasis to the economic aspects as well as the discussion of their possible implications for Latin America and the Caribbean. Analyses how cultural globalization generates a series of phenomena that modify the national socities' processes and their external policies.